A survey of design methods for material extrusion polymer 3D printing - Huang, Jiaqi; Chen, Qian; Jiang, Hao; Zou, Bin; Li, Lei; Liu, Jikai; Yu, Huangchao (Virtual and physical prototyping, 2020)
In recent years, additive manufacturing technology has been highly focused on its strong capability in complex geometry manufacturing and great suitability for customised product fabrication. Researchers have recognised the key role of additive manufacturing in leading the next-generation manufacturing, and have conducted extensive research from different aspects, including product design, process development, material modelling and many others. Several design-for-additive manufacturing methods have been proposed, specifically about design, and different computer-aided programmes have been developed, such as geometric modelling-based design, bio-inspired design, evolutionary algorithm-driven design and topology optimisation. However, authors have observed that many of these methods are named 'design for additive manufacturing' without specifying the exact additive manufacturing process. This could be problematic since a general design method cannot reflect the best practice given a specific additive manufacturing process. In this review paper, material extrusion polymer 3D printing is focused specifically. The motive of this paper is to conduct a literature survey about design methods for material extrusion polymer 3D printing, summarising the state of the art and pointing out the underdeveloped research topics; more importantly, some general design-for-additive manufacturing methods will be discussed, especially for their adaption to the material extrusion process.